Plasmepsin 4-Deficient Plasmodium berghei Are Virulence Attenuated and Induce Protective Immunity against Experimental Malaria - Spaccapelo, Roberta (American Society for Investigative Pathology, 2010)
Plasmodium parasites lacking plasmepsin 4 (PM4), an aspartic protease that functions in the lysosomal compartment and contributes to hemoglobin digestion, have only a modest decrease in the asexual blood-stage growth rate; however, PM4 deficiency in the rodent malaria parasite Plasmodium berghei results in significantly less virulence than that for the parental parasite. P. berghei Δpm4 parasites failed to induce experimental cerebral malaria (ECM) in ECM-susceptible mice, and ECM-resistant mice were able to clear infections. Furthermore, after a single infection, all convalescent mice were protected against subsequent parasite challenge for at least 1 year. Real-time in vivo parasite imaging and splenectomy experiments demonstrated that protective immunity acted through antibody-mediated parasite clearance in the spleen. This work demonstrates, for the first time, that a single Plasmodium gene disruption can generate virulence-attenuated parasites that do not induce cerebral complications and, moreover, are able to stimulate strong protective immunity against subsequent challenge with wild-type parasites. Parasite blood-stage attenuation should help identify protective immune responses against malaria, unravel parasite-derived factors involved in malarial pathologies, such as cerebral malaria, and potentially pave the way for blood-stage whole organism vaccines.